Development of a LC-MS/MS Method for the Simultaneous Detection of Tricarboxylic Acid Cycle Intermediates in a Range of Biological Matrices. (18th September 2017) - Al Kadhi, Omar; Melchini, Antonietta; Mithen, Richard; Saha, Shikha
Abstract : It is now well-established that perturbations in the tricarboxylic acid (TCA) cycle play an important role in the metabolic transformation occurring in cancer including that of the prostate. A method for simultaneous qualitative and quantitative analysis of TCA cycle intermediates in body fluids, tissues, and cultured cell lines of human origin was developed using a common C18 reversed-phase column by LC-MS/MS technique. This LC-MS/MS method for profiling TCA cycle intermediates offers significant advantages including simple and fast preparation of a wide range of human biological samples. The analytical method was validated according to the guideline of the Royal Society of Chemistry Analytical Methods Committee. The limits of detection were below 60 nM for most of the TCA intermediates with the exception of lactic and fumaric acids. The calibration curves of all TCA analytes showed linearity with correlation coefficients r 2 > 0.9998 . Recoveries were >95% for all TCA analytes. This method was established taking into consideration problems and limitations of existing techniques. We envisage that its application to different biological matrices will facilitate deeper understanding of the metabolic changes in the TCA cycle from in vitro, ex vivo, and in vivo studies.